2010
DOI: 10.1172/jci40380
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of activated protein C in murine endotoxemia is dependent on integrin CD11b

Abstract: Activated protein C (APC), the only FDA-approved biotherapeutic drug for sepsis, possesses anticoagulant, antiinflammatory, and barrier-protective activities. However, the mechanisms underlying its antiinflammatory functions are not well defined. Here, we report that the antiinflammatory activity of APC on macrophages is dependent on integrin CD11b/CD18, but not on endothelial protein C receptor (EPCR). We showed that CD11b/CD18 bound APC within specialized membrane microdomains/lipid rafts and facilitated APC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 46 publications
3
131
1
3
Order By: Relevance
“…Aberrations of monocyte/macrophage phenotype and function are increasingly recognized in SLE and animal models of the disease. Cao et al (30) showed that the anti-inflammatory activity of activated protein C on macrophages is dependent on integrin CD11b/CD18, but not on EPCR. They showed that CD11b/CD18-bound activated protein C, facilitated cleavage and activation of PAR-1, leading to enhanced production of sphingosine 1-phosphate and suppression of the proinflammatory response of activated macrophages (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrations of monocyte/macrophage phenotype and function are increasingly recognized in SLE and animal models of the disease. Cao et al (30) showed that the anti-inflammatory activity of activated protein C on macrophages is dependent on integrin CD11b/CD18, but not on EPCR. They showed that CD11b/CD18-bound activated protein C, facilitated cleavage and activation of PAR-1, leading to enhanced production of sphingosine 1-phosphate and suppression of the proinflammatory response of activated macrophages (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (30) showed that the anti-inflammatory activity of activated protein C on macrophages is dependent on integrin CD11b/CD18, but not on EPCR. They showed that CD11b/CD18-bound activated protein C, facilitated cleavage and activation of PAR-1, leading to enhanced production of sphingosine 1-phosphate and suppression of the proinflammatory response of activated macrophages (30). Activated protein C decreases the release of the MIP-1a from the monocytic cell line THP-1 and from human monocytes of septic patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…Proof for the major role for APC's cell-signaling actions (causing cytoprotective and immunoregulatory actions rather than its anticoagulant actions) came after 2006. 22,44,81,102,104 Hence, a 96-hour, low-dose wt-APC infusion was not optimally suited to harness APC's cell-signaling actions. We believe that bolus dosing is preferred to promote potent endothelial-barrier stabilization via PAR1 signaling and Rac1 activation and to alter gene expression profiles that promote antiapoptotic and anti-inflammatory activities.…”
Section: Apc: Translation To Clinical Therapiesmentioning
confidence: 99%
“…Thus, other PAR3-effector interactions are required for signal induction, diversification, and regulation ( Figure 3). PAR-effector complexes are hypothesized to involve the formation of PAR-PAR heterodimers and homodimers, 43 which may enable PARinduced transactivation of other PARs, integrate the transactivation of other GPCRs such as S1P1, 18,25,26 and incorporate cooperative cross talk with integrins such as Mac1 44,45 or other receptors such as ApoER2 46,47 or Tie2. 20,42,48 Formation of these complexes may achieve a signaling bias by promoting or discouraging the association of particular G-protein ensembles, 49,50 by recruiting b-arrestins, 30 or by incorporating nontraditional PAR signaling pathways via transactivations such as the activation of Tie2 by noncanonical activation of PAR3.…”
mentioning
confidence: 99%
“…Genetic inactivation of CD11b, PAR1, or sphingosine kinase-1, but not EPCR, abolished the ability of APC to suppress the macrophage inflammatory response in vitro. Using a LPS-induced mouse model of lethal endotoxemia, Cao et al (Cao, 2010) showed that APC administration reduced the mortality of wild-type mice, but not CD11b-deficient mice. Table 1.…”
Section: Other Receptorsmentioning
confidence: 99%